Ethics of continuous professional development in the promotion of health care quality - Altisent, Rogelio (Acta Bioethica, 2010)
Ethics has always being present in a more or less explicit way in health care quality; nevertheless, there has not been paid attention enough to the power of quality found in the ethical drive and attitudes of professionals who are leaders in improvement processes. The continuous professional development is a process which must accompany successive stages of professional life with different motivational moments and periods of crisis, for which understanding its ethical basis is convenient by reflecting about health care quality. Professionals who care patients also need attention to diagnose and overcome inertia, lack of initiative, skepticism and lack of self criticism situations. Health care quality can only be guarantee if professionals develop a satisfactory progress in their career, for which it is necessary that personal services and human resources of health care institutions devote their best energies in the promotion of their professionals.